Mathematical modeling and investigation of anomalies of the temperature field of the earth′s crust over oil and gas reservoirs: Fìz.-mat. model. ìnf. tehnol. 2020, 28:92-101 - Semerak, Mykhailo; Lyantse, Hanna (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2020)
In geothermal studies of oil and gas fields, temperature anomalies were found in the surface layers of the crust. In the paper, mathematical models of temperature fields of the Earth's crust over the oil and gas reservoirs have been constructed. The anomalies of the temperature field in the neutral layer depending on the depth of deposits, the capacity of the reservoir have been investigated using experimental data. A mathematical model of the Earth's crust has been also constructed taking into account its lithological structure. The influence of lithological heterogeneity of the layer on the temperature fields in the neutral layer has been investigated. References Dyakonov, D. I. (1958). Geotermiya v neftyanoj geologii. M. Gostoptehizdat. Lyalko, V. I., Mitnik, M. M., Vulfson, L. D., Shportyuk, Z. M. (1979). Geotermicheskie poiski poleznyh iskopaemyh. K:Naukova dumka. Kutas, R. I. (1978). Pole teplovyh potokov i termicheskaya model zemnoj kory. K.: Naukova dumka. Kutas, R. I., Gordienko, V. V. (1970). Teplovoe pole i glubinnoe stroenie Vostochnyh Karpat. Geofiz. sb. AN USSR, 34-35, 1970. Kutas, R. I., Gordienko, V. V. (1971). Teplovoe pole Ukrainy. Naukova dumka: Kiev. Lyubimova, E. A. (1966). Istochniki glubinnogo tepla Zemli i termicheskie svojstva zemnogo shara. Problemy glubinnogo teplovogo potoka, 3-30. Lyubimova, E. A. (1966). Ocenka raspredeleniya glubinnogo teplovogo potoka dlya yuga evropejskoj chasti SSSR. Problemy glubinnogo teplovogo potoka, 47-74. Yakovlev, B. A. (1979). Reshenie zadach neftyanoj geologii metodami termometrii. M.: «Nedra». Lialko, V. I., Popov, M. O. (Eds.). (2017). Suchasni metody dystantsiinoho poshuku korysnykh kopalyn. K: NAN Ukrainy. Liantse, H. T. (1998). Matematychna model rozpodilu temperaturnoho polia zemnoi kory pry vrakhuvanni neodnoridnosti yii budovy. Visnyk Derzhavnoho universytetu «Lvivska politekhnika». Prykladna matematyka, 337, 232-234. Lyance, A. T., Semerak, M. M. (1984). Issledovanie temperaturnogo polya v zemnoj kore pri nalichii neftegazovyh mestorozhdenij. Tezisy doklada Vsesoyuzn. Konf. «Issledovanie gravitacionnogo polya i prirodnyh resursov Zemli kosmicheskimi sredstvami», 120-121. Lyance, A. T., Semerak, M. M. (1986). Temperaturnoe pole v sloe s istochnikom tepla kusochno- postoyannoj moshnosti. Inzhenerno-fizicheskij zhurnal, 66, 34-85. Samarskij, A. A., Nikolaev, E. S. (1978). Metody resheniya setochnyh uravnenij. M.: Nauka. Proselkov, Yu. M. (1975). Teploperedacha v skvazhinah. M.: «Nedra».